Anti-Proliferative Activity of Poloxamer Cobalt Ferrite Nanoparticles against Human Prostate Cancer (DU-145) Cells: In-Vitro Study - Nazanin Oroskhani; Seyed Mohammad Amini; Sakine Shirvalilou; Mehdi Khodaie; Seyed Rabi Mahdavi (IET Nanobiotechnology)
Prostate cancer is the second most frequent type of cancer death in men. This study refers to the novel hyperthermia application of poloxamer-coated cobalt ferrite as a new approach for thermal eradication of DU-145 human prostate cancerous cells under a radio frequency magnetic field (RF-MF). The hydrothermal method was applied for the synthesis of cobalt ferrite nanoparticles. Then, the structure, size, and morphology of nanoparticle were characterized. The cytotoxicity of the synthesized nanoparticles and RF-MF exposure on DU-145 prostate cancer cells was investigated separately or in combination with colony formation methods and MTT [3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide] assay. Transmission electron microscopy (TEM) confirmed the spherical morphology of nanoparticles with a size of 5.5 ± 2.6 nm. The temperature of cells treated with nanoparticles under RF-MF reached 42.73 ± 0.2°C after 15 min. RF-MF treatment or nanoparticles have not affected cell viability significantly. However, the combination of them eradicated 53% ± 4% of cancerous cells. In-vitro hyperthermia was performed on human prostate cancer cells (DU-145) with cobalt ferrite nanoparticles at specific concentrations that demonstrated a decrease in survival fraction based on colony formation assay compared to cells that were treated alone with nanoparticles or with RF-MF.